One new species of Cymbella C.A. Agardh (Bacillariophyta) from high altitude lakes in the Hengduan Mountains of Southwest China - Liu, Qi (Array, 2021)
This paper describes a new species of the genus Cymbella C.A. Agardh from an alpine lake in the Hengduan Mountains of southwestern China. A detailed morphological description of the new species, named Cymbella luoyulanae sp. nov., is presented; the description is based on light and scanning electron microscopy. The main features of C. luoyulanae are strongly dorsiventral valves with strongly reverse-lateral raphe branches near the proximal ends, a large central area occupying approximately a half of the width with the valve and slit-like areolae comprising striae that may be unseriate or partially biseriate. The new species has morphological characteristics that resemble those of C. heihainensis Y.Li et Gong, C. modicepunctata Krammer and C. asiatica Metzeltin, Lange-Bertalot et Y.Li, but it differs from these three species in details of size, valve shape, striae density, central area, and number of stigmata.